2002
DOI: 10.1088/0031-9155/47/15/315
|View full text |Cite
|
Sign up to set email alerts
|

Scatter correction for positron emission mammography

Abstract: Abstract. In this paper we present a scatter correction method for a regularized list mode maximum likelihood reconstruction algorithm for the positron emission mammograph (PEM) that is being developed at our laboratory. The scatter events inside the object are modeled as additive Poisson random variables in the forward model of the reconstruction algorithm. The mean scatter sinogram is estimated using a Monte Carlo simulation program. With the assumption that the background activity is nearly uniform, the Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Simulation studies for a bPET system with improved chest wall coverage, lower average energy resolution, and higher photon sensitivity than DbPET/CT, however, revealed that the contribution to the total SF from OFOV activity is expected to be negligible. 46 Several artifacts were evident in images of a uniform cylinder even after application of all corrections. Most visible was a low magnitude concentric ring pattern (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Simulation studies for a bPET system with improved chest wall coverage, lower average energy resolution, and higher photon sensitivity than DbPET/CT, however, revealed that the contribution to the total SF from OFOV activity is expected to be negligible. 46 Several artifacts were evident in images of a uniform cylinder even after application of all corrections. Most visible was a low magnitude concentric ring pattern (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Because scatters and random events increase the number of counts of prompt data, they can improve the accuracy of the variance estimated by the data plug-in method (Qi and Leahy 2000). We note that imperfect scatter and random corrections can introduce additional variance in reconstructed images (Qi and Huesman 2002), but such corrections are unnecessary for lesion detection because these background events result in a common bias for both H 0 and H 1 hypotheses and doe not affect the lesion detectability for a well-trained observer. This is similar to the case where non-attenuation corrected PET images have been widely used before PET/CT was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the derivative of the reconstructed image x with respect to the background term r is 41,42 …”
Section: Iic Artifact Correctionmentioning
confidence: 99%